Needs Analysis of Oral and Written Communication in English for Nautical Students At Grade XII in SMKN 4 Bengkulu City - Rezky Atri Oktarin; syahrial syahrial; Ira Maisarah (Edu-Ling: Journal of English Education and Linguistics, 2022)
The design of this research is quantitative-qualitative descriptive research. The purpose of this research are first to analyze the needs of oral and written communication in English of nautical students in SMKN 4 Bengkulu and second to analyze the implementation of the students’ need. The subjects of this research are students of SMKN 4 Bengkulu 12th grade, English teachers in SMKN 4 Bengkulu, graduates of Nautical Study Program, and the stakeholders in the field of maritime. In this study, researcher used the needs analysis to find what are the need of oral and written of English for nautical students grade XII in SMKN 4 Bengkulu. The instruments that used in this study are questionnaires and interview. The result of the needs of oral and written of English for nautical students grade XII in SMKN 4 Bengkulu is the materials, topics, and activities that support their activities especially speaking and writing to work in the maritime field with simplified material that is suitable for beginner level and the needs can be implemented in lesson plan through the activity like monologue, watching film about cruise ship, and singing, but it will not appropriate with the curriculum set by the government.